Oral health in elderly: Assessment and current research status in Vietnam - Quan, Pham Nguyen (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Vietnam officially entered the aging population in 2011 with the elderly accounting for 10% of the total population. Aging not only influences overall health but also affects oral health. To evaluate oral function, various studies suggested using the term oral hypofunction with several criteria linking to swallowing, chewing, pronunciation activities. This study aims to give an overview of the assessment of oral health in the elderly and the research status of this issue in Vietnam. Within the limitations of the database search, oral hypofunction was evaluated clinically through 7 criteria. However, there have been no studies documenting this issue in Vietnam recently. For the preparation of an aged society in the future, studies about oral hypofunction should be encouraged.